Evaluasi Model CIPP pada Program Studi Al-Qur’an Intensif (SAINS) Universitas Negeri Makassar - Muh. Asdar; Munir Munir (Al-Musannif, 2021)
The main problem in this research is the evaluation of the Intensive Al-Qur'an Study (SAINS) program at UNM using the CIPP evaluation model. This study employs a qualitative research approach in evaluating the SAINS program at UNM using the CIPP evaluation model. The data sources of this research are information from members of the drafting panels of the SAINS-UNM program as well as information from the implemented documents of the SAINS program. Furthermore, the data collection methods used were interviews and documentation. Data processing and analysis techniques used in this research were three stages: data reduction, data presentation, and data conclusions drawing. The results of this study indicate that from its contextual aspect, the SAINS program at UNM has been done because 4 main reasons: to assist the lecturers of Islamic religion, to improve students’ ability in reading the Qur'an, to eradicate the illiterate of students of the Quran, and to maintain the spirit of reading the Quran among the students. In terms of its inputs, it is apparent that some improvements in particular areas are needed, particularly in planning and conducting curriculum development, tutor recruitment aspect, participants’ attendance, and financial planning and facility. In terms of its process, it was suggested that the program has been well conducted where all the previously planned activities were successfully accomplished. Finally, in terms of its product, it reveals that for those students who participated in the SAINS program, there is an increase in their ability to read the Quran.